2019
DOI: 10.1213/ane.0000000000003649
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Reality Analgesia in Labor: The VRAIL Pilot Study—A Preliminary Randomized Controlled Trial Suggesting Benefit of Immersive Virtual Reality Analgesia in Unmedicated Laboring Women

Abstract: This pilot study investigated the use of virtual reality (VR) in laboring women. Twenty-seven women were observed for equivalent time during unmedicated contractions in the first stage of labor both with and without VR (order balanced and randomized). Numeric rating scale scores were collected after both study conditions. Significant decreases in sensory pain -1.5 (95% CI, -0.8 to -2.2), affective pain -2.5 (95% CI, -1.6 to -3.3), cognitive pain -3.1 (95% CI, -2.4 to -3.8), and anxiety -1.5 (95% CI, -0.8 to -2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
60
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(64 citation statements)
references
References 14 publications
3
60
0
1
Order By: Relevance
“…One of the cornerstones of healthcare improvement, as formulated by the Institute of Healthcare Improvement, is with respect to the enhancement of patient experience 32 . In this regard, the findings of our pilot remain promising and in-line with other pregnancy-related studies which have demonstrated a high level of www.nature.com/scientificreports www.nature.com/scientificreports/ maternal satisfaction and acceptability for VR, with approval ratings between 77-82% 17,33 . This alludes to women being interested in and welcoming the addition of the technological medium into their pregnancy care.…”
Section: Discussionsupporting
confidence: 83%
“…One of the cornerstones of healthcare improvement, as formulated by the Institute of Healthcare Improvement, is with respect to the enhancement of patient experience 32 . In this regard, the findings of our pilot remain promising and in-line with other pregnancy-related studies which have demonstrated a high level of www.nature.com/scientificreports www.nature.com/scientificreports/ maternal satisfaction and acceptability for VR, with approval ratings between 77-82% 17,33 . This alludes to women being interested in and welcoming the addition of the technological medium into their pregnancy care.…”
Section: Discussionsupporting
confidence: 83%
“…Another study found VR significantly reduced pain during multiple stages of episiotomy repairs (hymen repair ES=0.74, 95%CI: 0.43, 1.04 and skin repair ES=1.00, 95%CI: 0.65, 1.36) in women after having their first baby compared to repair with no VR 35. The third study found VR significantly reduced the worst pain experienced during labor contractions compared to no VR (ES = unable to calculate) 37. The fourth study found no significant change in either average or worst pain felt during a cystoscopy procedure with the addition of VR (ES = unable to calculate) 36.…”
Section: Resultsmentioning
confidence: 95%
“…The median Total Body Surface Area (TBSA) was 15% (range TBSA of 2–55%).BPAcutePEDro 7/10Low-cost ASUS F5SL Business Laptop and LOGIC PC ATTACK 3 joystick for input and a HMD (eMagin Z800 3D visor)Patients played “Walt Disney's Chicken Little” PC game with immersive visual feedback and ability to interact with the game via joystick.20 minutes each (VR plus meds or just meds)Same number of repetitions and same exercises performed in the same plane by the same Physical Therapist without VR. Medications provided for both groups as per standard care.No significant difference could be detected between the two sessions (p = 0.13; MD = 2.09; 95% CI: -0.67 to 4.85)Pain during treatment.unable to calculateunable to calculateunable to calculateunable to calculateFrey, 201837RCT, within subjects cross over design27Range: 19-38Eligible patients were otherwise healthy women at ≥32 weeks’ gestation giving birth for the first time and in the first stage of labor with an anticipated vaginal delivery. Subjects were recruited from Michigan Medicine's Von Voigtlander Women's Hospital.MPRPAcutePEDro 6/10Samsung Gear VR HMD powered by a Galaxy S7 phone.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations